PERANCANGAN BOOKLET BANGUNAN BERSEJARAH DI KOTA PADANG - Elfi Tika Sari, Drs. Ariusmedi, M.Sn, Dra. Zubaidah, M.Pd (DEKAVE : Jurnal Desain Komunikasi Visual, 2013)
Purpose of this final work is (1) Designing the booklet as a medium to deliver information about the historic buildings remaining in the city of Padang both verbally and visually (2) To be introduced back to the people of the city of Padang on the historic buildings that are rich in value which is the starting pointof historical development of the city of Padang. As well, it can help the department of culture and tourism in promoting old buildings the city of Padang ,that can be an attractions in the city of Padang. Keyword: Padang City, historic buildings, booklet.